The development of Azerbaijani drama in Georgia (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article presents the literary landscape of Azerbaijan drama in Georgia and directions of dramatic development. This paper reveals the reasons for the delay of this genre development in comparison to other literary genres. Referring to the literary material, it discloses the idea of a circle-theme Azerbaijan drama in Georgia. An explanation of the artistic problems is represented in the plays. Interestingly, if you look at the Azerbaijan literary environment in Georgia in 1960–1980. Respectively, in local print literary journals, literary agencies do not meet the dramatic or comic works. Finally, it should be noted that the absence of a long time Azerbaijan National Theatre in Georgia, has made it clear and the dramatic trend of the Azerbaijan literature in relation to other genres are poorly developed. If we consider that in Azerbaijan dramaturgy towards prose and poetry was poorly developed, then everything becomes clear. But in recent years, written works in Georgian are encouraging and they inform about the prosperous future of Azerbaijan playwrights.
Keywords: drama; theater; Georgia; pieces; iterature